Yoghurt and Fennel Leaves Extract Based Liquid Soap Production Workshop at Al Ilyas Arjasari Boarding School In Bandung - Rum, Ira Adiyati; Sulaeman, Agus; Santoso, Rahmat; Dhiani, Yanni; Marliani, Lia; Iskandar, Deni (Inaba of Community Services Journal, 2024)
The Boarding School partner has many students but the habit of washing their hands before eating is not accompanied by washing with soap. This is a concern because washing with soap ensures the disappearance of pathogenic microbes. Teaching the importance of washing hands with soap before meals aims to raise awareness about the benefits of maintaining hygiene and supplementary nutrition could improve health. We trained the pupils in the Boarding School to make liquid hand-washing soap and yoghurt to stimulate a hygienic lifestyle, provide in-house supplementary nutrition, and gain economic benefit from the products. The hygienic lifestyle knowledge was delivered through a presentation in an open-class setting, while soap and yoghurt production skills were taught by an in-hand workshop, followed by post-monitoring for both activities. The yoghurt was produced by fermentation, and the soap was made by formulating a macerate of fennel leaf extracted into hand-washing soap. The pupils’ knowledge of hygienic lifestyles improved with an average score of 68 to 90.